2011
DOI: 10.3109/02656736.2011.561270
|View full text |Cite
|
Sign up to set email alerts
|

Improved power steering with double and triple ring waveguide systems: The impact of the operating frequency

Abstract: Simulations showed that a 130-MHz two-ring waveguide system yields significantly higher tumour temperatures compared to 70-MHz single-ring and double-ring waveguide systems. Temperatures were further improved with a 130-MHz triple-ring system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…Since 900 MHz was the maximum frequency simulated in this work, however, it is likely that the globally optimal frequency of the treatment energy is in fact greater than 900 MHz. This conclusion echoes previous studies that have found that MW frequencies are well suited to deep HT of small tumours [1820,39]. Our uSAF results indicate that high frequencies are well suited to both deep and shallow head and neck HT: At 900 MHz, uSAFs ranged from 16.6 (deep midbrain tumour #12) to 100.1 (shallow brain tumour #8).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Since 900 MHz was the maximum frequency simulated in this work, however, it is likely that the globally optimal frequency of the treatment energy is in fact greater than 900 MHz. This conclusion echoes previous studies that have found that MW frequencies are well suited to deep HT of small tumours [1820,39]. Our uSAF results indicate that high frequencies are well suited to both deep and shallow head and neck HT: At 900 MHz, uSAFs ranged from 16.6 (deep midbrain tumour #12) to 100.1 (shallow brain tumour #8).…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, the optimal frequency was found to vary with the volume of the target: Higher (smaller) frequencies tended to do better for small (large) volumes. Kok et al [20] also showed in simulations that devices with multiple z-ring tend to do better than single-ring designs for a pelvic target. Besides these studies, other simulation studies have focussed on modelling existing devices, such as the BSD Sigma 60 applicator (Pirexar, Salt Lake City, UT) [21] and the Sigma Eye applicator (Pirexar, Salt Lake City, UT) [2224].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they can be used to intelligently interpolate temperatures between sparsely measured points. Thermal modeling has also been used successfully to study the influence of water bolus cooling on expected temperature distributions of superficial heat applicators (137-140) and to investigate the influence of uncertainties in thermal parameters on applicator choice for deep-regional hyperthermia (24, 53, 141). With continued development, temperature modeling is expected to become useful for prediction of thermal dose and treatment outcome.…”
Section: Temperature Distribution Simulation Techniquesmentioning
confidence: 99%
“…Another important application of treatment planning is to compare simulated heating patterns for different hyperthermia systems, either for development of a new prototype or to compare different heating techniques for a specific patient or tumour site [87][88][89][90][91][92][93][94]. For this application, the qualitative reliability of pre-treatment planning can be used to compare heating characteristics of different hyperthermia systems to select the optimal system for tumour heating.…”
Section: Discussionmentioning
confidence: 99%